MEMBANGUN KARAKTER EMPATI ANAKMELALUI PROGRAM JUMKOH ( JUM’AT SODAKOH ) DI SDN CIPEYEUM 04 CIANJUR - Ilmiah, Danabillah; Rizkiansyah, Dani; Latipah, Euis (LPPM STAI Al-Azhary Cianjur, 2024)
This study aims to analyze the implementation of the Friday Sodakoh program in developing empathy and social responsibility among students at SDN Cipeyeum 04 Cianjur. The Friday Sodakoh program is a charitable initiative held every Friday, where students are encouraged to set aside a portion of their pocket money to be donated to those in need. This research uses a qualitative approach with a descriptive method to illustrate the program's implementation and its impact on students' character development. Data collection techniques include interviews with Islamic Religious Education (PAI) teachers, observations, and documentation. The results show that the program received a positive response from students, who demonstrated enthusiasm and high motivation to participate. The program not only helps students develop empathy and social concern but also enhances their communication, critical thinking, and analytical skills. Additionally, parental involvement plays an important role in supporting the program’s success. However, challenges such as ensuring consistent participation from all students and ensuring that donations are distributed appropriately remain. Overall, the Friday Sodakoh program positively impacts students' character development and supports moral education in schools.